Man into Woman : The First Sex Change, A Portrait of Lili Elbe - มะลิทอง รัชตพงศ์ (Journal of the Faculty of Arts, Silpakorn University, 2020)
แนะนำหนังสือเรื่อง Man into Woman : The First Sex Change, A Portrait of Lili Elbe